The Use of Cryopreserved Medications from the Feto-Placental Complex as a Method for Treating Infertility Caused by Chronic Endometritis: a Case Report - Feskov, Oleksandr; Konoplia, Lina; Feskova, Anna (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):295